Utilization of AI Chat Bot as a Chemistry Learning System on Atomic Structure to Improve Students' Understanding of Concepts: Systematic Review - Bunga Adinda Putri; Isti Yunita (Dinasti Research, 2026)
This study aims to analyze the role and implementation of artificial intelligence (AI)-based chatbots in chemistry learning at the high school level, particularly in strengthening understanding of abstract concepts such as atomic structure. This study uses a systematic literature review approach to 18 relevant scientific articles from 2016 to 2026 originating from reputable international journals, preprints, and empirical research results in the fields of educational technology and chemistry education. The results of the study indicate that the use of AI chatbots in high school chemistry learning can be grouped into two main categories: studies that focus on the development of AI-based learning systems and studies that emphasize the implementation of chatbots as learning aids such as virtual tutors, concept exploration agents, simulation media, and scientific writing support. In general, AI chatbots have been proven to improve student learning motivation, understanding of chemical concepts, critical thinking skills, and independent learning skills. However, several limitations were also found, such as inaccurate information, hallucination phenomena, lack of adaptation to the high school pedagogical context, and the risk of student dependence on AI technology. Specifically for atomic structure, there has been no research specifically and in-depth on the implementation of AI chatbots, leaving a significant research gap. Therefore, the development of a more contextual, targeted, and tailored AI chatbot-based chemistry learning model is needed, tailored to the characteristics of high school students.